Development and Validity Test of Fuel Station Consumer Safety Behavior Questionnaire - Wibowo, Aryo; Lestari , Fatma; Modjo, Robiana (Journal La Medihealtico, 2023)
Fuel Stations are facilities for selling fuel to the public which has a potential hazard and a high risk of accidents. During 2017-2018 there were 120 gas station accidents in Indonesia. Additionally, 29 fuel accidents occurred in 2022, most of them involving consumer vehicles. Previous studies have explored fuel station safety by examining its safety climate, health risks to workers, risk and fire assessments. Study on consumer behavior in fuel stations has not yet been discovered. Therefore, this study attempts to fill the gap by developing a Fuel Station Consumer Safety Behavior (FSCSB) Questionnaire. The aim of this study is to introduce a novel instrument to assess fuel station consumer safety behavior and assess its validity and reliability. The first phase of this study uses a qualitative approach on developing the questionnaire through literature review, content validity with field experts and face validity with actual fuel station consumers. In the second phase, a quantitative approach for validity and reliability analysis was carried out by calculating Pearson's Product Moment and Cronbach's Alpha on each variable. All questionnaire items passed the Pearson's validity test, but 3 items did not meet minimum Cronbach's Alpha criterion and have been removed. The final result is a novel FSCSB Questionnaire with 21 items. The questionnaire can be used as a reference for future research with a larger number of respondents.